Study on the correlation between serum β2-microglobulin, cystatin C, urea levels and hypertensive nephropathy in elderly undergoing health checkups - ZHU Li; FU Xia; MAO Mingying; MA Yan; WANG Yumei; XU Hongxia; JI Chengjie; WU Tao (Yixue xinzhi zazhi, 2025)
Objective Exploring the association between serum β2-microglobulin levels, serum cystatin C, serum urea, and hypertensive nephropathy in the elderly population undergoing physical examinations.Methods Selecting the elderly population who underwent physical examinations at the People's Hospital of Jianyang City from February 2021 to May 2024 and were diagnosed with kidney disease as the research subjects. They were divided into hypertensive nephropathy group and non-hypertensive nephropathy group based on whether they had hypertension. Analyzing the influencing factors and diagnostic efficacy of hypertensive nephropathy through Logistic regression and receiver operating characteristic curve (ROC) analysis, and analyze the correlation between renal indicators and hypertensive nephropathy through Kendall analysis.Results A total of 210 elderly individuals with kidney disease were included, with 70 cases in the hypertensive nephropathy group and 140 cases in the non-hypertensive nephropathy group. The levels of β2-microglobulin, serum cystatin C, and serum urea in the hypertensive nephropathy group were higher than those in the non-hypertensive nephropathy group (P